2018
DOI: 10.1002/ecs2.1923
|View full text |Cite
|
Sign up to set email alerts
|

Activity and resource selection of a threatened carnivore: the case of black bears in northwestern Mexico

Abstract: Abstract. Management and conservation strategies for endangered species require information on their temporal and spatial behavioral and habitat use relationships. We evaluated activity patterns and resource selection of black bears in northwestern Mexico. We surveyed 29 localities with 1450 camera traps stations from 2009 to 2013 in the states of Sonora and Chihuahua, Mexico. In each locality, we calculated the proportion of diurnal, nocturnal, and crepuscular activity through a kernel density estimator based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 56 publications
(178 reference statements)
1
8
0
Order By: Relevance
“…Elevation and mean vegetation productivity were the most important covariates regardless of data type, the latter being influential for ursid space use at broad scales in other areas (e.g., Duquette et al, 2017; Lara‐Díaz et al, 2018). Tye et al (2017) and Coxen et al (2017) also compared citizen and professional data for developing SDMs and found similar predictions and estimates of habitat relationships.…”
Section: Discussionmentioning
confidence: 98%
“…Elevation and mean vegetation productivity were the most important covariates regardless of data type, the latter being influential for ursid space use at broad scales in other areas (e.g., Duquette et al, 2017; Lara‐Díaz et al, 2018). Tye et al (2017) and Coxen et al (2017) also compared citizen and professional data for developing SDMs and found similar predictions and estimates of habitat relationships.…”
Section: Discussionmentioning
confidence: 98%
“…Because location data were not available for feral horses and cattle, we used data from our camera array to create RSFs through a used‐unused design (Manly et al 2002, Lara‐Diaz et al 2018). We created RSFs for each species using generalized linear mixed models with the glmmTMB package in R (Brooks et al 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Colorado Plateau and Southern Rocky Mountains, Datil-Mogollon Section, Mexican Highlands, and Sacramento Section) and populations separated by desert and isolated by distance had lower gene flow (e.g., Trans-Pecos and Boulder Mountain). Because female black bears are highly philopatric, the effect of distance on gene flow may be governed by their behavior, but also mediated by long-distance dispersal events by male bears with male bears also having been shown to select against ruggedness (Apps et al, 2006;Johnson et al, 2015;Lara-Díaz et al, 2018;Pelletier et al, 2011).…”
Section: Notesmentioning
confidence: 99%
“…Black bears are forest obligates and have evolved morphological and behavioral adaptations associated with exploiting forest stands (Herrero, 1972) and they require thermal refugia (Lara-Díaz et al, 2018) because they are susceptible to hyperthermia (Sawaya et al, 2017). We modeled these features using canopy height (canopy), percent canopy (percan), and water bodies (water) as canopy provides thermal cover and water is necessary for thermoregulation, especially if bears crossed more inhospitable land cover such as desert.…”
Section: Environmental Variablesmentioning
confidence: 99%